The effects of climate change event characteristics on experiences and response behaviors: a study of small woodland owners in the Upper Midwest, USA - Denny, Riva C. H.; Fischer, A. Paige (Frontiers in Climate, 2023)
Whether and under what conditions people are compelled to adapt to climate change is a question of significant policy and scholarly importance. However, little is known about the influence of the characteristics of the climate change events with which people have experience on people's decisions to modify their behavior to reduce risk. We investigated this topic through quantitative analysis of survey data from small woodland owners in areas affected by three types of severe events known to be exacerbated by climate change: droughts, storms, and tree insect and disease outbreaks. We found that events with faster onset and termination speeds and greater visibility were associated with people’s self-reported experiences of these events and decisions to undertake various practices out of concern about them, likely because events with these characteristics are easier to observe. These findings have implications for scientific understanding of the climate change conditions that compel people to perceive risk and act.